REVIEW OF METHODS FOR INVESTIGATION OF ELECTRICAL PARAMETERS OF SEMICONDUCTOR MATERIALS - N. R. Abdulkhalikova; U. R. Rustamov (Galaxy International Interdisciplinary Research Journal, 2023)
The paper presents a variety of modern trends and prospects for methods for measuring the electrical parameters of a solid body. The demand for the work is due to the fact that the development of research methods can make a further contribution to the progress of alternative energy, contributing to the expansion of the range of semiconductor materials with new properties. General information on bridge and non-contact methods for studying electrical parameters is given. A forecast of the development of microwave and magnetic induction methods for studying the electrical parameters of semiconductor and other promising materials is shown. The significant progress achieved in recent years in the development of these research methods is shown. The work is of interest to researchers involved in the synthesis of new materials for the development of alternative energy.